A call for regulatory reform to make work experience accessible rather than an obstacle. (December 2022) - Hewitt, Anne; Grenfell, Laura
It is widely recognised that a lack of work experience can impede university students seeking graduate employment and that many tertiary students face significant barriers in securing work experience. Drawing on existing research, this article analyses these barriers, and considers the consequences of this inequity for affected individuals as well as for broader Australian society and the economy. The article proposes various 'do-able' reforms to the regulation of work integrated learning in tertiary education and student-finance schemes which would go some way to reducing these barriers.